Application of metabolomics and network analysis to reveal the ameliorating effect of four typical “hot” property herbs on hypothyroidism rats - Wang, Yang-Yang; Sun, Yan-Ping; Yang, Bing-You; Wang, Qiu-Hong; Kuang, Hai-Xue (Frontiers in Pharmacology, 2022)
The ‘hot’ property herb is commonly applied in cold syndrome. Unfortunately, the underlying mechanisms of the ‘hot’ property herbs on hypothyroidism has not been investigated. This study is aiming to probe the activities of the four typical ‘hot’ property herbs on hypothyroidism, and four typical ‘cold’ herbs set as contrasting experiments. Firstly, the physical sign, thyroid function and metabolism profile (multivariate statistical analysis) were assessing the difference between the four typical ‘hot’ property herbs and four typical ‘cold’ property herbs. H&E staining were used to confirmed the influence of the typical ‘hot’ property herbs on hypothyroidism. A metabolomics approach combine with network pharmacology were explored the effected mechanism of the typical ‘hot’ property herbs on hypothyroidism. The metabolites pathway and target-associated metabolites were verified Na+/ K+-ATP enzyme and ACC1, which detected by commercial kits, and the gene expression of UCP-1 was detected by RT-PCR. It is firstly proved that the four typical ‘hot’ property herbs effectively ameliorate the physical sign, thyroid function and metabolism profile in hypothyroidism rats, whereas the four typical ‘cold’ property herbs showed no benefit. Moreover, the four typical ‘hot’ property herbs regulated through PI3K-Akt signaling pathway, Ca 2+- AMPK signaling pathways to promoting lipid metabolism and energy metabolism, as well via purine metabolism and tryptophan metabolism to improve the declined energy metabolism and thyroid hormone levels. And the levels of UCP-1, Na+/ K+-ATP enzyme and ACC1 were ameliorated by the four typical ‘hot’ property herbs in hypothyroidism rats. In a word, metabolomics strategy combine with network pharmacology was successfully performed and well interpreted the mechanism of the four typical ‘hot’ property herbs on hypothyroidism based on the theory of ‘cold and hot’ property of TCM.